Intelligent Metadata and Context-Aware MDM for Dynamic Decision-Making - Viswakanth Ankireddi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Master Data Management (MDM) is experiencing a transformative evolution through the integration of artificial intelligence and advanced analytics capabilities. This comprehensive article explores how AI-driven metadata management and context-aware systems are revolutionizing traditional MDM approaches, enabling organizations to make more informed and dynamic decisions. The article examines the implementation of intelligent MDM systems across various industries, highlighting improvements in data quality, operational efficiency, and strategic decision-making. The article demonstrates how predictive analytics and contextual intelligence enhance data governance, customer experience, and supply chain management. Furthermore, it analyzes the technical requirements and organizational readiness factors crucial for successful MDM implementation, providing insights into the future of enterprise data management practices.
Keywords: Artificial Intelligence; Master Data Management; Predictive Analytics; Data Governance; Digital Transformation